Optimization of Aluminum Leaching from Alunite Ore with NaOH Using Response Surface Methodology (RSM) - Babayeva, Parvana; Heydarov, Arif; Turan, M. Deniz; Nizamoglu, Hasan; Demir, Tugrulhan (Springer, 2025)
With the advancement of technology, the depletion of primary resources is accelerating. While approximately 90% of global bauxite reserves are utilized for aluminum production, alunite ore has gained attention as a potential alternative due to its aluminum content and the relatively easily removable impurities it contains. However, for alunite to be considered an economically viable source, undesirable components such as phosphorus must be effectively removed. In this study, the selective extraction of aluminum from alunite was investigated through leaching with a sodium hydroxide (NaOH) solution. The effects of leaching time, temperature, and liquid-to-solid ratio were examined using the Box-Behnken design within the framework of Response Surface Methodology (RSM). The optimization criterion was defined as maximizing aluminum solubility while minimizing phosphorus dissolution. The optimal process conditions were determined as follows: NaOH concentration of 7%, leaching duration of 30 min, leaching temperature of 69 degrees C, and a liquid-to-solid ratio of 56 mL/g. Under these conditions, aluminum extraction efficiency was measured at 89%, whereas phosphorus extraction was limited to 18%. X-ray diffraction (XRD) analysis of the raw alunite ore and the leach residue obtained under optimal conditions indicated a reduction in the intensity of aluminum-associated peaks. Furthermore, scanning electron microscopy (SEM) analysis revealed the formation of an irregular morphological structure in the residue.
Keywords: Alunite; Aluminum; Phosphorus; Leaching; RSM